CHRONIC UNPREDICTABLE STRESS-INDUCED BEHAVIORAL AND ELECTROPHYSIOLOGICAL ALTERATIONS AND ITS AMELIORATIVE EFFECT BY MYRICETIN MICROEMULSION - G, Sakthivel; Karunya M, Deva; P, Prajisha; Cs, Keerthipriya; R, Ravindran (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study is designed to investigate the effects of chronic unpredictable stress (CUS) on electrophysiological and behavioral alterations in male Wistar albino rats and its ameliorating effect by myricetin-microemulsion (MYR-ME). Materials and Methods: Adult Wistar male albino rats were exposed to CUS for 21 days and treated with MYR-ME (10 mg/kg) for 21 days by oral administration. All the experimental animals were tested for anxiety and cognitive behavior by open-field behavior, light/dark test, eight-arm radial maze, spontaneous alteration T-maze, novel object recognition test, plasma corticosterone level, and electrophysiological activity. Results: The rats which were exposed to CUS showed memory impairment, increased anxiety, decreased novel explorations, deleterious effect on decision-making, increased corticosterone level, increased brain wave frequency and amplitude, and also heart rate. Whereas, CUS with MYR-ME-treated group showed a protective effect against CUS-induced behavioral alterations, electrophysiological activity, and corticosterone levels, which is characterized by the enhancement of cognitive function, decreased anxiety and improved decision-making, novel exploration, decreased corticosterone, and electrophysiological activity. Conclusion: From the present study, it is shown that MYR-ME may act as a potential anxiolytic and nootropic compound against CUS-induced alterations.